Exploring the pharmacist’s role in pregnancy care: perceptions, practices, competencies, and barriers - Anan S. Jarab; Walid Al-Qerem; Karem H. Alzoubi; Yukta Sughand; Shrouq R. Abu Heshmeh; Yazid N. Al Hamarneh; Judith Eberhardt (Critical Public Health)
Pregnant women often worry about medication effects on their unborn child, leading to inadequate care and potential risks to maternal and fetal health. Research on community pharmacists’ role in prenatal care is limited. This cross-sectional study used a validated, self-administered survey distributed to 405 pharmacists across the United Arab Emirates to evaluate their perceptions, practices, competencies, and barriers in pregnancy care. Data were analyzed using quantile regression to identify associations between demographic and professional factors. Female pharmacists had more favorable perceptions (coefficient = 1.508) and higher competencies (coefficient = 0.457). Pharmacists without pregnancy-related postgraduate training reported less favorable perceptions (coefficient = −2.201) and lower practice levels (coefficient = −0.852). Higher practice levels, reflecting frequent engagement in key pregnancy care activities, were associated with spending more time with patients (coefficient = 0.204) and having favorable perceptions (coefficient = 0.488). Conversely, lower practice levels, indicating less frequent involvement, were linked to less experience and lack of training. Key barriers included insufficient training and limited knowledge of updated guidelines. The findings reflect wider global challenges and highlight the need for training and guidance to strengthen pharmacists’ contribution to maternal health.